Border Imperialism and Exclusion in Canadian Parliamentary Talk about International Students - McCartney, Dale M. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2020)
Although there is a rich critical literature examining international student policy in Canada, very little of it considers the views of Members of Parliament. MPs have limited direct influence over international student policy, but their policy talk about international students defines the context within which such policy is developed. For that reason Parliamentary debate deserves study. This paper examines MPs’ discussion of international students between 1984 and 2019, tracing themes in MP policy talk over the globalization era. It finds that MPs evince remarkably consistent attitudes towards international students. Throughout the period MP policy talk shows that Parliamentarians saw international students as outsiders who were only ofvalue to the extent that they could be made to serve Canada’s economic or political agenda. The uniformity of this attitude and the lack of dissenting voices suggest that MPs’ views may be a significant barrier to reforming international student policy in Canada.